1970
DOI: 10.1007/bf00282699
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cycloheximide and 6-methylpurine on in vivo compatible and incompatible pollen tube growth in Lilium longiflorum

Abstract: Cycloheximide, a potent inhibitor of protein synthesis, placed in styles of Lilium longiflorum at 10(-4) M in stigmatic exudate before, 6, or 12 hr after compatible or incompatible pollination retarded all pollen tube growth. An inhibitor of RNA synthesis, 6-methylpurine, placed in the style at 10(-4) M in stigmatic exudate before, 6, or 12 hr after pollination restricted compatible pollen tube growth to lengths not significantly different thanincompatiblepollen tubes in treated or nontreated styles. While pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1971
1971
1981
1981

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…When carried in stigmatic exudate and injected at or after pollination, these substances tended to significantly retard compatible pollen tube growth at concentrations which did not affect incompatible tube lengths. tube growth (16). In the 26 experiments conducted with these materials (Table 4), compatible pollen tube growth was more sensitive than incompatible to RNA synthesis inhibition, suggesting that compatible pollen tube development requires RNA synthesis unnecessary for normal incompatible pollen January 1981 109 bExperiments with treatments reducing pollen tube growth to near zero cannot be subjected to standard analysis of variance since the variance is correlated to treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When carried in stigmatic exudate and injected at or after pollination, these substances tended to significantly retard compatible pollen tube growth at concentrations which did not affect incompatible tube lengths. tube growth (16). In the 26 experiments conducted with these materials (Table 4), compatible pollen tube growth was more sensitive than incompatible to RNA synthesis inhibition, suggesting that compatible pollen tube development requires RNA synthesis unnecessary for normal incompatible pollen January 1981 109 bExperiments with treatments reducing pollen tube growth to near zero cannot be subjected to standard analysis of variance since the variance is correlated to treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Using various inhibitors of RNA or protein synthesis and either stigmatic exudate or distilled water as carriers, we found that both compatible and incompatible pollen tubes require protein synthesis for normal growth, that only compatible tubes require RNA synthesis, and that the style requires RNA synthesis to produce the selfincompatibility reaction in L. longiflorumt (14,16). The purpose of this presentation is to report the effects on pollen tube growth of a number of exogenous materials injected into L. longiflorum styles.…”
Section: Introductionmentioning
confidence: 99%